A favorable effect of hydroxychloroquine on glucose and lipid metabolism beyond its anti-inflammatory role. (August 2014) - Hage, Mirella P.; Al-Badri, Marwa R.; Azar, Sami T.
Hydroxychloroquine (HCQ), a commonly used antimalarial drug in rheumatic diseases, has shown favorable metabolic effects on both glucose control and lipid profiles. We describe a case of a young woman with type 1 diabetes whose glycemic control was optimized with the introduction of HCQ as a treatment for her Sjogren syndrome in addition to a subtle yet measurable improvement in her lipid profile. An increasing body of evidence supports the beneficial impacts of HCQ in various ancillary conditions, including diabetes mellitus and dyslipidemia. However, mechanisms of action responsible for these effects remain ill-defined and may include alterations in insulin metabolism and signaling through cellular receptors. These favorable metabolic effects of HCQ and further understanding of underlying mechanisms may provide an additional rational for its use in rheumatic diseases, conditions associated with an elevated cardiovascular risk.